Gender Roles And Contraceptive Self-Efficacy In Contraceptive Use - Ummu Kulsum; Dyan Evita Santi (AGUSPATI RESEARCH INSTITUTA, 2023)
Abstract - Unmet need is a couple of childbearing age who do not want to have more children or who want to arrange and space pregnancies but do not use contraception. Unmet need for family planning is influenced by many factors, such as lack of husband's support and culture. In Indonesia, the husband's decision to allow his wife is an important guideline for his wife to use contraception, besides that contraceptive self-efficacy is a predictor that influences behavior related to contraceptive use. Case report: This case study examines a subject, Mrs. E, 30-year-old woman, G5P0130 33/34 weeks of gestation, Pre-eclampsia, Bad Obstetric History (BOH). Delivery was carried out by SC and for medical indications, the provider had motivated the installation of contraception using an IUD (Intra Uterine Device) which is a long-term and safe method of contraception for women with a history of pre-eclampsia. Mrs E's husband disapproves of the use of the IUD contraceptive method, although they do not plan to have children in the near future. The husband is the main decision maker so that the husband's consent in choosing the contraceptive method is important. Mrs. E do not use contraception until 4 months after delivery. In her 5th month, Mrs. E took the initiative to use simple family planning using the condom method and interrupted coitus. Conclusion: The husband's role is still the main influencing factor for the mother in determining and choosing the contraception methode, however, women who have high self-efficacy have the ability to initiate and use contraception